Integration of aerogammaspectrometric and ground electromagnetic data in a copper occurrences region in the extreme northwest of the camaquÃ basin, southern brazil - Pereira, Henrique Garcia; Ferreira, Francisco José Fonseca; Moreira, César Augusto [UNESP] (UNESP - Universidade Estadual Paulista, 2021)
In the different phases of prospective campaigns for metallic minerals such as copper, Geophysics acts as a support tool both in the recognition of new exploratory targets and the expansion of known deposits, due to the achievement of contrasts in physical properties between mineralizations and host rocks. The present study presents the results of the aerogammaspectrometry recognition phase, followed by the detailing of potential copper targets through the inductive terrestrial electromagnetic method in an area covered by the occurrences named Victor Teixeira and Capão Grande, both located to the interior of the municipality of Caçapava do Sul, in the state of Rio Grande do Sul, Brazil. The Victor Teixeira occurrence is part of the metamorphic rocks of the Sul-Riograndense Shield, while the one in Capão Grande has as its host the Camaquã Basin’s volcano-sedimentary lithotypes. The outcrop mineralization of both occurrences comprises carbonate disseminations predominantly in fractures. The aerial radiometric data allowed the demarcation of potassium-enriched areas associated with hydrothermal alteration products as indirect guides for the location of copper targets. The correlation of this potassium guide with high concentrations of thorium was also a promising indication. The apparent conductivity data obtained along the aeroradiometric targets made it possible to suggest the presence of copper sulfides in conductive areas in the metamorphic basement’s schists and the arcosian conglomeratic sandstones of the Camaquã Basin.
Integração de dados aerogamaespectrométricos e eletromagnéticos terrestres em região de ocorrências de cobre no extremo noroeste da bacia do camaquã, sul do brasil
Keywords: Aerogammaspectrometry; Inductive electromagnetic profiles; Mineral prospecting; Sul-riograndense shield